Wrist injuries in climbers - Schöffl, V.; von Schroeder, H.; Lisse, J.; El-Sheikh, Y.; Küpper, T.; Klinder, A.; Lutter, C. (The American Journal of Sports Medicine, 2023)
Background: Acute and chronic injuries to the wrist are among the most common sport-related complaints of climbing athletes but have not been extensively evaluated in this population. Therefore, it is important to categorize climbing injuries to the wrist, analyze risk factors, and assess treatment outcomes.